2001
DOI: 10.1093/occmed/51.7.456
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in industrial workers under thermal stress on extended shift lengths

Abstract: A field investigation to examine the fatigue levels in industrial workers working extended (10, 12 and 12.5 h) shifts under significant levels of thermal stress was conducted on 45 male underground miners. Studies were conducted both before and after a major change to the working-in-heat protocol used at the operation. Prior to the change, shortened (6 h) shifts had been used when thermal conditions exceeded certain values. This reduced shift length was removed and replaced with other protocols. Heart rates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 17 publications
4
19
0
Order By: Relevance
“…So, the trend of lowered average aerobic capacity compared to general population and other occupations was in well concert with the results obtained by other investigators [12–15]. With respect to mining population abroad, the mean value was quite comparable with the Spanish [16], Polish [17] and Australian miners [18]. However, the aerobic capacities of South African miners (47 mL/kg/min) [19] and some other Spanish mine workers (43.2 mL/kg/min) [20] as found by other investigators was reported to be far higher than the observed value.…”
Section: Discussionsupporting
confidence: 87%
“…So, the trend of lowered average aerobic capacity compared to general population and other occupations was in well concert with the results obtained by other investigators [12–15]. With respect to mining population abroad, the mean value was quite comparable with the Spanish [16], Polish [17] and Australian miners [18]. However, the aerobic capacities of South African miners (47 mL/kg/min) [19] and some other Spanish mine workers (43.2 mL/kg/min) [20] as found by other investigators was reported to be far higher than the observed value.…”
Section: Discussionsupporting
confidence: 87%
“…It was revealed that the average V O2max of the younger and older groups was 38.13 ± 2.4 and 36.04 ± 2.3 ml/kg/min, which was lower than that for Indian industrial workers (46.6 ml/kg/min) [29]. The value was found to be lower than that for Australian (39.1 ml/kg/min) and Spanish (43.2 ml/kg/min) miners too [21,30].…”
Section: Heaviness Of the Job And Cardiovascular Fitness Of The Trammermentioning
confidence: 62%
“…These estimated values were used to assess RAS and were crossexamined against certain recommended criteria of physical strain that allowed a better evaluation of strain in relation to different parameters. The physical strain of the present underground tramming job in terms of HR could be compared with underground coalface miners of poorly mechanized mines in Austria [20] and metalliferous miners in Australia [21]. Exertion was also reported for drillers and diggers of Bulgarian opencast mines [22].…”
Section: Physical Strain Of the Tramming Jobmentioning
confidence: 99%
“…(4,6,8,(27)(28)(29)(30)(31)(32) In particular, those studies that have measured core temperature responses report moderate but stable core temperature elevations for different work environments of various degrees of mechanization. (6,33) In the present study, we found that mean core temperature during the work shift increased and was maintained at comparable levels over the course of the work shift, with values ranging between 37.20 and 37.42 • C for the different jobs.…”
Section: Discussionmentioning
confidence: 99%